Efficient Delivery of Dengue Virus Subunit Vaccines to the Skin by Microprojection Arrays - David A. Muller; Alexandra C.I. Depelsenaire; Ashleigh E. Shannon; Daniel Watterson; Simon R. Corrie; Nick S. Owens; Christiana Agyei-Yeboah; Stacey T.M. Cheung; Jin Zhang; Germain J.P. Fernando; Mark A.F. Kendall; Paul R. Young (Vaccines, 2019)
Dengue virus is the most important arbovirus impacting global human health, with an estimated 390 million infections annually, and over half the world’s population at risk of infection. While significant efforts have been made to develop effective vaccines to mitigate this threat, the task has proven extremely challenging, with new approaches continually being sought. The majority of protective, neutralizing antibodies induced during infection are targeted by the envelope (E) protein, making it an ideal candidate for a subunit vaccine approach. Using truncated, recombinant, secreted E proteins (sE) of all 4 dengue virus serotypes, we have assessed their immunogenicity and protective efficacy in mice, with or without Quil-A as an adjuvant, and delivered via micropatch array (MPA) to the skin in comparison with more traditional routes of immunization. The micropatch contains an ultra-high density array (21,000/cm2) of 110 μm microprojections. Mice received 3 doses of 1 μg (nanopatch, intradermal, subcutaneous, or intra muscular injection) or 10 μg (intradermal, subcutaneous, or intra muscular injection) of tetravalent sE spaced 4 weeks apart. When adjuvanted with Quil-A, tetravalent sE vaccination delivered via MPA resulted in earlier induction of virus-neutralizing IgG antibodies for all four serotypes when compared with all of the other vaccination routes. Using the infectious dengue virus AG129 mouse infectious dengue model, these neutralizing antibodies protected all mice from lethal dengue virus type 2 D220 challenge, with protected animals showing no signs of disease or circulating virus. If these results can be translated to humans, MPA-delivered sE represents a promising approach to dengue virus vaccination.